The Efficacy Of Digital Pedagogy In The Professional Development Of Teaching Competence - Kamarudin, Kamarudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study investigates the efficacy of digital pedagogy in enhancing the professional development of teaching competences among fourth-semester students of the English Education Study Program at Mandalika University of Education. Using a quantitative research design, data were collected from 25 participants through a structured 20-item questionnaire assessing key aspects of teaching competence, including digital communication, instructional design, and technology integration. The results show that digital pedagogy supports the growth of teaching competences by offering flexibility, access to diverse resources, and opportunities for independent learning. A majority of students reported improved skills in designing teaching materials and utilizing digital platforms for educational communication. However, several challenges were identified, such as limited real-time interaction and technical issues like unstable internet connectivity. While 60% of students perceived digital pedagogy as effective, others expressed the need for stronger pedagogical support and infrastructure. The study concludes that digital pedagogy has substantial potential to contribute to the professional preparation of future educators, provided it is implemented with careful planning, adequate technical support, and interactive instructional strategies.